Analisis Penerapan Keterampilan Membuka-Menutup Pelajaran Oleh Guru Pendidikan Agama Kristen dalam Meningkatkan Motivasi Belajar Siswa Kelas XI SMA Negeri 1 Pangaribuan Tahun Ajaran 2019/2020” - nurani giotmarito sitinjak (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The purpose of this study was to determine the magnitude of the achievement of the implementation of opening and closing skills lessons by teachers PAK in improving students' motivation in class XI SMA Negeri 1 Pangaribuan Academic Year 2019/2020. The hypothesis of this research is the application of opening and closing skills lessons by teachers PAK in improving students' motivation in class XI SMA Negeri 1 Pangaribuan Academic Year 2019/2020 75% of the 100% expected. The population is all class XI students of SMAN 1 Pangaribuan school year of 2019/2020 the Protestant amounted to 274 people. The research sample determined by random sampling (random) 20% of 274 is 55 people. This research method is quantitative descriptive inferential methods. The instrument used in this study was a questionnaire. Test the hypothesis by using the formula t obtained by value t-count=35.002 t-table = 2.000. The value t-count is in the region H0 rejection and acceptance curve Ha. It can be concluded that the application is accepted research hypothesis opening and closing skills lessons by teachers PAK in improving students' motivation in class XI SMA Negeri 1 Pangaribuan Academic Year 2019/2020 75% of the 100% expected. Achievement of the application of opening and closing skills lessons by teachers PAK in improving students' motivation in class XI SMA Negeri 1 Pangaribuan Academic Year 2019/2020 is 3.49 are in both categories with a large percentage of 87.37% in the category is very strong. Keywords : Implementation, Opening-Closing Skills Lessons, Motivation